Analisis Nukleotida dan Homologi Sekuens Fragmen Gen p72 (B646L) Virus African Swine Fever Virus (ASF) Asal Kota Kupang - Sanam, Maxs U. E.; Gelolodo, Maria Aega; Toha, Larry R. W. (JURNAL KAJIAN VETERINER, 2022)
African Swine Fever (ASF) is an important infectious disease in pigs caused by African Swine Fever Virus (ASFV). Despite not being zoonotic, this disease has the potential to severely affect the socioeconomic conditions in the impacted regions. The majority of pig farmers in Indonesia, particularly those in Kupang City, that raise pigs in backyards or on a small scale, experience the impact of ASF's effects. Early in 2020, the ASF cases were confirmed in Timor Island, including the Kupang City area in Nusa Tenggara Timur (NTT) Province. The molecular information on ASFV in this area is still limited. In order to determine the homology and nucleotide analysis using BLAST NCBI, the ASFV p72 (B646L) gene fragment sequence from Kupang City was compared to ASFV p72 (B646L) gene segments from other parts of Indonesia and several other Asian countries. The results of nucleotide analysis and sequence homology of the original ASFV p72 (B646L) gene fragment from Kupang City showed a high level of homology to the ASFV p72 (B646L) gene fragment from West Java, North Sumatra, and several Asian countries. The findings from this study indicate that the source of ASF viral transmission across different regions may be comparable. Therefore, to prevent the dissemination of ASF, strict biosecurity measures must be implemented along with monitoring of animal and product transportation.